Measuring The First-Year Students’ Ability of English Study Program on English Grammar in Academic Year 2023/2024 - Lumban Raja, Viator; Pangaribuan, Jontra Jusat; Naibaho, Lisna (Journal of Applied Linguistics, 2025)
This study investigated the grammar proficiency of first-year students enrolled in the English Study Program during the 2023/2024 academic year. A quantitative descriptive approach with a post-test-only design was employed, involving 22 participants. Data were collected through a standardized 30-item multiple-choice test that assessed 17 key grammar topics, including tenses, passive voice, conditionals, and relative pronouns. The results indicated that students achieved a mean score of 45.14, categorized as "poor" according to the university's academic guidebook. None of the participants reached the "good" category threshold of 71, with scores ranging from 20 to 69. Topic-specific analysis revealed inconsistencies in performance, with only six test items correctly answered by 72% of students. The most challenging topics identified were causative verbs, conditionals, and gerunds, which require higher-order thinking skills, such as understanding sentence structure and contextual usage. Further analysis showed that students from state schools outperformed their peers from private schools, with mean scores of 52.8 and 38.75, respectively, although neither group met the threshold for "good" proficiency. These findings suggest significant gaps in students’ grammar knowledge, particularly in complex topics, and raise concerns about the effectiveness of current teaching methods. Keywords : English grammar; proficiency; teaching strategies